(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2021)
This article is an attempt to define the values and moral norms held by young people, that is their moral condition, by analysing the attitudes of the surveyed secondary school graduates from Puławy towards the Decalogue, the attitudes towards general and specific moral norms, the duties of a Catholic regarded as the most important as well as moral authorities and role models. These issues were discussed in the light of sociological research conducted in Puławy in the years 1994-2009-2016. The sociological analyses carried out show that some of the secondary school graduates from Puławy are sceptically-minded towards the norms of Catholic ethics. Even the moral norms of the Ten Commandments are not considered to be a rigorously significant moral code for ca. 30% of young people in Poland. Some of them question the Decalogue, others adjust its importance depending on their specific situation in life. Permissive and relativist tendencies intensify even more in relation to individual attitudes and behaviours. For 31 of the assessed behaviour patterns – according to the integrative indicator – 20.2% of the respondents assessed these behaviours in the “neutral” categories and 16.8% – justified breaking the commandments. Secondary school graduates from Puławy are guided first of all by their own conscience when solving conflicts, to a much lesser extent – by their parents’ or friends’ advice. About half of the surveyed did not notice in their environment any significant persons whom they could value or regard as exemplary.